2010
DOI: 10.1002/anie.201003302
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Molecular Architectures by the Controlled Self‐Assembly of a β‐Peptide Foldamer

Abstract: Nature utilizes the self-assembly of monomeric units by multiple noncovalent interactions for the construction of complex functional systems.[1] In recent decades, a variety of peptide-based scaffolds, which range from simple aromatic dipeptides to small protein fragments, have been studied in order to understand the underlying mechanism and mimic this process to create artificial nano-and microstructures. [2][3][4][5][6] Because of the intrinsic large conformational flexibility of short-length peptides, amphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
64
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 53 publications
1
64
0
Order By: Relevance
“…Although a variety of peptide-based scaffolds have been studied, most of the reported peptides self-assemblies are limited to round shapes such as spheres, tubes, and rods. In a recent work [113], Lee et al reported the first example of finite molecular architectures formed by the self-assembly of a helical β-peptide in aqueous solution (Fig. 10).…”
Section: Molecular Systems Used In Self-assembly and Soft Nanomatermentioning
confidence: 99%
See 1 more Smart Citation
“…Although a variety of peptide-based scaffolds have been studied, most of the reported peptides self-assemblies are limited to round shapes such as spheres, tubes, and rods. In a recent work [113], Lee et al reported the first example of finite molecular architectures formed by the self-assembly of a helical β-peptide in aqueous solution (Fig. 10).…”
Section: Molecular Systems Used In Self-assembly and Soft Nanomatermentioning
confidence: 99%
“…(Reproduced with permission from Ref. [113], Copyright 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)…”
Section: Figmentioning
confidence: 99%
“…[1] As the concentration of P123 was increased, an evolution in foldecture shapes away from the primitive shape F 0 was observed. [1] As the concentration of P123 was increased, an evolution in foldecture shapes away from the primitive shape F 0 was observed.…”
mentioning
confidence: 96%
“…[1] An otable architectural feature shared by these assemblies is the presence of ac ommon four-fold symmetry axis despite the different and unusual 3D shapes,s uch as windmill, petal, square bar, molar tooth, and rectangular tube. [1] An otable architectural feature shared by these assemblies is the presence of ac ommon four-fold symmetry axis despite the different and unusual 3D shapes,s uch as windmill, petal, square bar, molar tooth, and rectangular tube.…”
mentioning
confidence: 99%
“…Foldectures are an ew class of crystalline peptidic material with unprecedented topological complexity derived from the rapid and non-equilibrium aqueous phase self-assembly of foldamers.W ehave demonstrated that it is feasible to obtain av ariety of three-dimensional (3D) foldecture shapes from as et of b-peptide foldamers with identical 12-helical secondary structures by simple variation of the self-assembly conditions. [1] An otable architectural feature shared by these assemblies is the presence of ac ommon four-fold symmetry axis despite the different and unusual 3D shapes,s uch as windmill, petal, square bar, molar tooth, and rectangular tube. This observation raised the fundamental question of whether 4-fold symmetry is intrinsic to foldectures or is instead determined by foldamer secondary structure,w ith new and useful foldecture morphologies potentially available through the choice of ad ifferent foldamer secondary structure.S uch ar elationship,i fp resent, would offer ag eneral and useful method to design foldectures using foldamer secondary structure as the basic unit, with specific shapes and diverse functions that more closely resemble biological architectures.…”
mentioning
confidence: 99%